Kyai's Transformative Leadership In Pesantren-Based on Campus - Naili Yaturrochmah; Siti Aimah; Muhammad Imam Khaudli (EDUTEC : Journal of Education And Technology, 2024)
The objective of this research is to analyze the characteristics of transformative leadership by a Kyai at a pesantren-based campus, specifically at Universitas Nurul Jadid (UNUJA) in Paiton, Probolinggo. This qualitative research utilizes a case study methodology. Data were collected through in-depth interviews, participant observation, and documentation. The data analysis process involved data reduction, data display, and conclusion drawing. The study is grounded in Bernard M. Bass's theory of transformational leadership and Michael Armstrong's performance theory. The results indicate that Kyai Abdul Hamid Wahid, as the rector of Universitas Nurul Jadid, implements transformative leadership in several ways: 1) as an Agent of Change, he transformed IAI Nurul Jadid, STT Nurul Jadid, and STIKES Nurul Jadid into Universitas Nurul Jadid; 2) as a Master Planner, he formulated the milestones for Universitas Nurul Jadid as an international Islamic university.